Camelina Production in Florida - Ramdeo Seepaul; David Wright; Sheeja George; Ian Small (EDIS)
This publication discusses camelina adaptability, stand establishment, pest and disease management, and nutrient management. Written by Ramdeo Seepaul, David Wright, Sheeja George, and Ian Small, and published by the UF/IFAS Agronomy Department, revised July 2022.